Effect of surfactant addition and viscosity of the continuous phase on flow fields and kinetics of drop formation in a flow-focusing microfluidic device. (2nd February 2022) - Kiratzis, Ioannis; Kovalchuk, Nina M.; Simmons, Mark J.H.; Vigolo, Daniele
Highlights: Neck kinetics develop in slow initial stage and a faster second stage. Thinning exponent is dependent on surfactant concentration and transport dynamics. Marangoni phenomena during necking reduce velocities close to the interface. Fluid recirculation during expansion depends on continuous phase viscosity. Abstract: Droplet formation in a flow focusing microfluidic device was studied for capillary numbers between 10 −4 and 10 −1 . The addition of a cationic surfactant to the dispersed phase and the effect of the continuous phase viscosity on droplet size, neck kinetics and flow fields inside the drop was investigated. Droplet size decreased with an increase of the capillary number following a power law with an exponent dependent on drop confinement. At 1–3 ms before pinch-off, the neck thinning rate is dependent on surfactant concentration and increases closer to pinch-off. For the 96 mPa s continuous phase, the two-fluid Stokes regime is observed with an effective interfacial tension smaller than the equilibrium value, suggesting a negative contribution of Marangoni stresses. During necking, velocities along the neck interface for the surfactant laden cases are smaller due to Marangoni phenomena. During expansion, increased fluid velocities and recirculation are observed.